Academic Writing in Context: Possibility of Professional Development of University Professors - HERNÁNDEZ VARGAS, ELIZABETH; MARÍN CANO, MARTHA LILIANA (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The research reported in this article corresponds to the results of a documentary analysis (Galeano, 2012) of “The academic writing in context: possibility of professional development of university professors”. The study aims, on the one hand, to identify, through research in academic writing, the different theoretical and methodological perspectives, and, on the other hand, to analyze the relationship that exists between academic writing and the professional development of university professor. To this end, 50 documen ts dating from 2006 to 2016 were analyzed and published in different countries, such as Chile, Colombia, Mexico, Portugal, Argentina, Venezuela, the United States, Spain and Canada. The results show the interest of the researchers due to the difficulties that exist in the writing process, the scriptural formation of the university professor, the writing as a complex task, the use of academic writing, the explanations to the problems of reading and writing in the student leaving aside teachers, and student l earning and teachers' didactics